Consider the Multi-Objective Topology Optimization Design of a Space Structure Under Complex Working Conditions - Feng Jia; Pan Gao; Aodong Mo (Mathematics)
In order to improve the stiffness and dynamic performance of the connecting frame and realize the lightweight, based on the topological optimization theory of the variable density method, the mathematical model of topology optimization of the connecting frame under multiple working conditions is established by the compromise programming method, considering the influence of thermal, dynamic, and static loads of the connecting frame, the weights of each working condition are decomposed by analytic hierarchy process, a whole is effectively improved, and the first-order frequency of the connecting frame is increased from 1700 Hz to 1932 Hz, which is increased by 13.6%. Two sets of comparative experiments are used to verify the effectiveness of the simulation results and the rationality of using the multi-objective topology optimization design method for the lightweight design of space structures under complex working conditions. The conclusion can provide a theoretical reference for the lightweight design of supporting components for spacecraft and other systems.